2016
DOI: 10.3390/ijerph13100949
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant Staphylococcus aureus and Other Staphylococcus Species in Raw Meat Samples Intended for Human Consumption in Benin City, Nigeria: Implications for Public Health

Abstract: The present study was designed to characterize methicillin-resistant staphylococci from raw meat. A total of 126 meat samples were obtained from open markets between February and April, 2015. Antimicrobial susceptibility testing was carried out using the disc diffusion method. Molecular profiling was conducted using 16S rRNA, mecA, nuc, and PVL gene signatures were detected by polymerase chain reaction assay. Fifty isolates of methicillin-resistant Staphylococcus spp. were detected in 26 (52%) pork, 14 (28%) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…It has been previously reported that antimicrobials are widely used in food animal production settings for treatment/prevention and for growth promotion [9,11]. Studies have also revealed that 50%-90%…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been previously reported that antimicrobials are widely used in food animal production settings for treatment/prevention and for growth promotion [9,11]. Studies have also revealed that 50%-90%…”
Section: Discussionmentioning
confidence: 98%
“…Resistance to antimicrobials by pathogenic bacterial isolates can also be a consequence of the ability of the organisms to harbour resistant genes and transmit these genes within bacterial populations via horizontal gene transfer and mobile genetic elements (transposons, plasmids, etc.) [10,11]. This is a crucial issue as these organisms might migrate into the food chain resulting in food infection or directly to humans resulting in difficulties to treat infections [12].…”
mentioning
confidence: 99%
“…S. aureus are now generally resistant to methicillin and most other β-lactam antimicrobials. Methicillin resistance in staphylococci is mediated usually by mecA gene carried on staphylococcal chromosomal cassette (SCCmec) (15) which codes for altered penicillin-binding protein 2a or 2' (PBP2a or 2') with low binding affinity to betalactamase resistant penicillins such as oxacillin and methicillin, and other betalactam antimicrobials (16).…”
Section: Introductionmentioning
confidence: 99%
“…On phenotypic evaluation for the presence of mecA gene, 37.2 % (58) of the S. aureus were resistant to oxacillin, which according to Feng-Jui et al (2014), mecA promoter mutations play an important role in determining the level of oxacillin resistance, hence, high resistance to oxacillin is an indication of MRSA. The study of Raghabendra et al (2017) in Nepal who observed 31.82% resistance to oxacillin among MRSA S. aureus isolated from poultry samples is in line with this study.…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant S. aureus (MRSA) with this base pair has been reported to be capable of causing a wide range of food poisoning due to the production of endotoxins, pneumonia, post-operative wound and nosocomial infections (Cuny et al, 2010). The report of Igbinosa et al (2016) in Benin City, Edo State, who observed 52% mecA incidence in pork, 28% in beef and 20% in chicken samples substantiate the possibility of isolating mecA encoded MRSA from food sample and this correlated with the objective of this study. Report has shown that poultry associated MRSA have been linked to increased morbidity and mortality in patients and increased medical care costs as a result of zoonotic transfer, particularly in developing countries where there are limited and generally unaffordable therapeutic options (Otalu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%